GREEN ACCOUNTING, CARBON EMISSION DISCLOSURE, AND FIRM VALUE IN INDONESIA: THE MODERATING ROLE OF GOOD CORPORATE GOVERNANCE - Theresia Siwi Kartikawati; Zulham Alfarizi; Haryati Haryati; Lilis Listiyawati (Bajang Institute, 2026)
Indonesia, as a developing country with several carbon-intensive industries such as mining, energy, and manufacturing, faces significant challenges in achieving a sustainable green economy. In response to increasing environmental concerns, companies are encouraged to implement green accounting practices and disclose carbon emissions as part of their sustainability commitments. However, the effectiveness of these practices in enhancing firm value may depend on the quality of corporate governance. This study aims to examine the effect of green accounting and carbon emission disclosure on firm value, with Good Corporate Governance (GCG) serving as a moderating variable. The study uses mining companies participating in the Corporate Performance Rating Assessment Program (PROPER) issued by the Ministry of Environment and Forestry during the 2020–2023 period. Data were analyzed using multiple regression and moderated regression analysis. The results indicate that green accounting and carbon emission disclosure do not individually affect firm value significantly. However, both variables simultaneously have a positive effect on firm value. Furthermore, Good Corporate Governance significantly moderates the relationship between green accounting and firm value, but does not moderate the relationship between carbon emission disclosure and firm value. These findings suggest that the integration of sustainability practices and strong governance mechanisms can enhance investor confidence and support long-term firm value.